Futures commodities prices and media coverage - Miguel Almánzar; Máximo Torero; Klaus von Grebmer (University of Bonn, Center for Development Research (ZEF), 2013)
In this paper we examine the effects of media coverage of commodity prices increases and decreases on the price of the commodity and how media coverage in other commodities affects prices. We provide evidence of the relationship between media coverage and its intensity to the price level of agricultural commodities and oil futures. We find that price movements are correlated with the media coverage of up movements, or increase in prices. The direction of the correlation is robust and positive for media coverage of increases in prices, and negative for decreases in prices. These results point to increases in prices being exacerbated by media attention by 8%. In addition, we find interesting countervailing effects of this reinforcing price pressures due to media activity in the previous days. Finally, we find that even though volatility is higher for the set of days where there is media coverage, this hides important dynamics between media coverage and volatility. The volatility of market adjusted returns is negatively correlated with the media coverage, both up and down media coverage. Markets days with intense media coverage of commodity prices tends to have lower volatility.
Keywords: G13; Q11; C53; C58; D84; D82; 330; prices; future prices; volatility; media; food security; time series; commodity returns